If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 + 4 = 11 + 9x Reorder the terms: 1 + 4 + 5x = 11 + 9x Combine like terms: 1 + 4 = 5 5 + 5x = 11 + 9x Solving 5 + 5x = 11 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 5 + 5x + -9x = 11 + 9x + -9x Combine like terms: 5x + -9x = -4x 5 + -4x = 11 + 9x + -9x Combine like terms: 9x + -9x = 0 5 + -4x = 11 + 0 5 + -4x = 11 Add '-5' to each side of the equation. 5 + -5 + -4x = 11 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 11 + -5 -4x = 11 + -5 Combine like terms: 11 + -5 = 6 -4x = 6 Divide each side by '-4'. x = -1.5 Simplifying x = -1.5
| 3m+2m+4n+3n= | | 9/4x=1/16 | | 2/3x=140 | | 1=12x-8 | | 5x+8=6x-18 | | 10/9c=-81 | | P-3.2=7.6 | | 7.3y-5.8=51.9 | | 53-2x=5x-17 | | 15+9n=9-n | | 2(7x+2)=-12 | | 2/3z=1/21 | | 50=5ln(3x+7) | | 84=2*35+2*w | | X(8-1)=18 | | -1=2x-8 | | -x/4-5=-8 | | -15+t=20 | | 4/3m=8/15 | | a/3-7=10 | | 25x+2000=2000 | | -7(2-6x)-4x=23+x | | -2+3=-(x+6) | | 84+36=93 | | 3*x+sqrt(3)=3*sqrt(3) | | 1/10=1/5y | | 2f-3=11f-24 | | -8+6x-10-8x= | | -7(6x+7)=-42x+49 | | (2x-2)*x/2=182 | | 2x+13x=40 | | -7(6x+7)=-42x |